Midwifery professionalisation and practice: Influences of the changed registration standards in Australia. Issue 1 (February 2016) - Gray, Michelle; Rowe, Jennifer; Barnes., Margaret
Abstract: Background: In June 2010 the Australian Health Practitioner Agency unified the national registration of health professionals in Australia and introduced a separate register for midwives. Standard registration renewal requirements aimed to provide safe, competent practitioners. These new conditions created the impetus for practitioners to consider how they meet the re-registration standards for either their nurse or midwifery register/s. Question: How are midwives responding to the changed re-registration conditions for registration renewal? Methods: Longitudinal case study design. A purposive sample of 24 midwives from five states was recruited. 20 took part in individual interviews over two re-registration periods. 4 midwives were interviewed in a focus group to verify the findings. Findings: Three themes captured issues and tensions about registration and midwifery practice. They are Rotation, Restriction and Extension. Conclusion: This paper has shown how the re-registration conditions and standards post 2010 have generated discourse around registration renewal. The simultaneous introduction of regulatory and legislative changes has resulted in the construction of categories within contemporary midwifery practice that do not necessarily align with the Nursing and Midwifery Board of Australia (NMBA) requirements for re-registration. Further research is recommended to examine the continuing influence and impact of the changes on the Australian midwifery workforce.